Influence of the Maillard Reaction on the Properties of Gelatin/Zein Nanofibers Loaded with Dihydromyricetin Prepared by Electro-Blowing Spinning - Hui Xiang; Runtian Wu; Man Xiao; Jianhui An; Longchen Shang; Yexing Tao; Lingli Deng (Biomolecules)
This study investigated gelatin/zein nanofibers loaded with dihydromyricetin (0–20%, relative to protein weight), before and after the Maillard reaction (60 °C with 50% relative humidity for 6 h). Scanning electron microscopy and diameter distribution analysis indicated that dihydromyricetin incorporation increased the fiber diameter from 692 ± 133 to 922 ± 121 nm, while the nanofibers maintained a uniform morphology following the Maillard reaction. Fourier transform infrared spectroscopy revealed that dihydromyricetin formed hydrogen bonds with protein molecules. X-ray diffraction results indicate that dihydromyricetin was uniformly dispersed within the gelatin/zein nanofibers. The addition of dihydromyricetin improved the thermal stability of the nanofibers. Furthermore, after the Maillard reaction, the nanofibers with dihydromyricetin demonstrated enhanced water resistance. Mechanical testing revealed that nanofibers containing 20% dihydromyricetin after the Maillard reaction exhibited a considerably higher elastic modulus of approximately 90 MPa. In addition, nanofibers containing dihydromyricetin exhibited notable antioxidant activity and antibacterial properties against Escherichia coli and Staphylococcus aureus. In summary, gelatin/zein nanofibers containing high concentrations of dihydromyricetin exhibited favorable physical and functional properties, supporting their suitability as effective delivery systems for dihydromyricetin in active packaging applications.